John Adams, minimalism and beyond - Berrow, Jim.; Gavin, Barrie; Adams, John, 1947-; Films for the Humanities (Firm) (Princeton, NJ : Films for the Humanities & Sciences, 1992)
Discusses the minimalist composer, John Adams, and his music.
Film originally made in 1988?
VHS format.
Keywords: Adams, John, -- 1947-; Composers -- United States -- Interviews